If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(x + -3) = (x + 9)(x + -4) Reorder the terms: (3 + x)(x + -3) = (x + 9)(x + -4) Reorder the terms: (3 + x)(-3 + x) = (x + 9)(x + -4) Multiply (3 + x) * (-3 + x) (3(-3 + x) + x(-3 + x)) = (x + 9)(x + -4) ((-3 * 3 + x * 3) + x(-3 + x)) = (x + 9)(x + -4) ((-9 + 3x) + x(-3 + x)) = (x + 9)(x + -4) (-9 + 3x + (-3 * x + x * x)) = (x + 9)(x + -4) (-9 + 3x + (-3x + x2)) = (x + 9)(x + -4) Combine like terms: 3x + -3x = 0 (-9 + 0 + x2) = (x + 9)(x + -4) (-9 + x2) = (x + 9)(x + -4) Reorder the terms: -9 + x2 = (9 + x)(x + -4) Reorder the terms: -9 + x2 = (9 + x)(-4 + x) Multiply (9 + x) * (-4 + x) -9 + x2 = (9(-4 + x) + x(-4 + x)) -9 + x2 = ((-4 * 9 + x * 9) + x(-4 + x)) -9 + x2 = ((-36 + 9x) + x(-4 + x)) -9 + x2 = (-36 + 9x + (-4 * x + x * x)) -9 + x2 = (-36 + 9x + (-4x + x2)) Combine like terms: 9x + -4x = 5x -9 + x2 = (-36 + 5x + x2) Add '-1x2' to each side of the equation. -9 + x2 + -1x2 = -36 + 5x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -9 + 0 = -36 + 5x + x2 + -1x2 -9 = -36 + 5x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -9 = -36 + 5x + 0 -9 = -36 + 5x Solving -9 = -36 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -9 + -5x = -36 + 5x + -5x Combine like terms: 5x + -5x = 0 -9 + -5x = -36 + 0 -9 + -5x = -36 Add '9' to each side of the equation. -9 + 9 + -5x = -36 + 9 Combine like terms: -9 + 9 = 0 0 + -5x = -36 + 9 -5x = -36 + 9 Combine like terms: -36 + 9 = -27 -5x = -27 Divide each side by '-5'. x = 5.4 Simplifying x = 5.4
| 3/5+25 | | Y2-4y+4/y2+3y-10 | | 5y+3y=7y+6 | | 22+9x=35-14x | | .25x+.40-.40x=.31 | | 2x(x+3)=-7 | | 3.14(9x^2+12x+4)=0 | | -12=-9p-3p | | x^2-8x-320=0 | | 6y-5=-23 | | x+2-(2x+1)=3 | | -5(-4-a)=3a+8 | | 3x-5/4+2=2x/3 | | 2/3a=14 | | 30x+43=7(4x+5)+2x+8 | | .25x+9=.5 | | 3(3-y)/5=-y | | 7t-4=10c+14 | | 3s-8+7s=0 | | 3/10x+2/5=-1/2 | | -3(4x-9)+3=-12x+30 | | 4y-2=y+10 | | (3/10)x+(2/5)=(-4) | | 0.14(y-5)+0.02y=0.20y-0.5 | | X-14=5x+12 | | 3/10x+2/5=-4 | | y=-5/4x+27.5 | | 8-y=6 | | (3y+12)+(y+12)+41=0 | | 2(x+6)+7=19 | | 3(3w+5)=6(w-1) | | 12r-14=5(2-r) |